Cross-linked perforated honeycomb membranes with improved mechanical and chemical properties. (23rd December 2016) - Zhong, Qi-Zhi; Zhang, Li-Wei; Ou, Yang; Wu, Bai-Heng; Wan, Ling-Shu; Xu, Zhi-Kang
Abstract : Robust and self-standing honeycomb-patterned membranes are prepared by both the rapid vapor diffusion cross-linking of S2 Cl2 and thiol–ene click chemistry. Abstract : Ultrathin perforated honeycomb-patterned membranes show promise for high-resolution separation, in which the mechanical strength and chemical stability of membranes are very important. Here we report facile and versatile modification methods for preparing cross-linked honeycomb membranes with tunable mechanical and chemical properties. Commercially available polystyrene- b -polyisoprene- b -polystyrene (SIS), which contains double bonds for post modification, together with an amphiphilic block copolymer was utilized as the membrane-forming material. Robust and self-standing honeycomb membranes were obtained by the rapid vapor diffusion cross-linking of S2 Cl2 in 5 min. X-ray photoelectron spectroscopy (XPS) and energy dispersive X-ray spectroscopy (EDX) results demonstrate effective cross-linking. The cross-linked membranes show excellent resistance to organic solvents and other harsh environments. Water flux measurements indicate that the cross-linked membranes can endure trans-membrane pressure as high as 0.12 MPa. The cross-linked membranes are stable in a wide temperature range. Another cross-linking method based on thiol–ene click chemistry is also proved to be able to form robust membranes with both improved stabilities and controllable surface properties. Moreover, the cross-linked perforated honeycomb membranes can be used for separation under higher operation pressure.